Choosing hope : moving forward from life's darkest hours - Roig-DeBellis, Kaitlin; Fisher, Robin Gaby (G.P. Putnam's Sons, 2015)
Roig-Debellis is the first-grade teacher at Sandy Hook Elementary School who saved her entire class of fifteen six- and-seven-year-olds from the tragic events that took place on December 14, 2012, by piling them into a single-occupancy bathroom within her classroom, mere feet from the brutal and indiscriminate massacre taking place outside the door. Despite the unimaginably painful experiences she endured, she has chosen to share her experience with others, in the hope that they too can find light in dark moments. There is no moving on, but there is always moving forward. And how we move forward is a choice.